UV Spectrophotometric Development and HPLC Methods for Estimation of Paracetamol in Oral Syrup Formulation: Validation, Comparison and Application - Hussein, Abdulhakeem D. H (International Journal of Psychosocial Rehabilitation, 2020)
In the present study, a high performance liquid chromatography (HPLC) and developed ultra-violet spectroscopic (UV) methods were validated and compared for detection the quantity of paracetamol forms that are taken orally . HPLC method was performed at ambient temperature using C18 column with a mobile step composed of water and methanol (70:30, v / v). The mobile phase was flow at a rate of 1 mL/min and UV-detector detection was achieved at 243 nm. UV method was completed with δmax at 256 nm. The results of the study were confirmed according to ICH guidelines, and the plotted standard curves show strong linearity for HPLC and UV-Vis with regression coefficients of 0.9978 and 0.9998 respectively. For both methods the detection limit (LOD) and the quantification limit (LOQ) were determined. Accuracy were 102.91, 100.00 and 99.78% for HPLC method, and 102.91, 100.00 and 99.78% for UV method. The methods were also found precise and robust (RSD< 2%). Assay of four oral syrup formulation was detected by both methods . There was no statistically important difference between the power obtained from both used methods by paired t-test and F-test at a meaning level of 5%. Thus the standard addition method used in UV-Vis was as safe as that used in RP-HPLC and; Therefore, there was no need to waste time, energy and money using HPLC unless it was justified by an emergency.